Comparison of Annealing and Normalizing Cooling in Ferrous Metal Melting to Make Baffle Plates on Strength and Hardness Values Using the Three-Point Bending Method and Rockwell Hardness - Fransnazoan Sitorus; Muhammad Firmansyah; Dejoi Irfian Situngkir; Emil Salim P Siregar; Nuzuli Fitriadi (Jurnal Inotera, 2026)
Metal casting is one of the forming processes widely used in the manufacture of industrial components, including baffle plates installed in babcock and wilcox type boilers, due to its high flexibility and reliability. The study aims to compare the effects of annealing and normalizing heat treatment processes on the strength and hardness of cast metal baffle plates. The annealing process involves heating the material to a certain temperature followed by slow cooling, while the normalizing process uses air cooling at a controlled rate. The hardness of a material must be known, especially for materials undergoing construction during operation, while the flexural strength represents the maximum bending stress that the material can withstand under external loads without deformation. Hardness was measured using the rockwell hardness method, and flexural strength was tested using the three-point bending method. The results showed that the average flexural strength of the annealed specimens was 59 kgf/mm², which was lower than that of the normalized specimens at 66 kgf/mm². In addition, the average hardness of the normalized specimens reached 113.66 HRC, slightly higher than that of the annealed specimens at 108.22 HRC. These findings indicate that the normalizing process increases the flexural strength and hardness more effectively than the annealing process.